Penerapan Metode AHP dan OCRA Dalam Pengambilan Keputusan Menentukan Santri Berprestasi - Mochammad Ichsan; Putri Aisyiyah Rakhma Devi (Jurnal Pendidikan Informatika (EDUMATIC), 2021)
The selection of outstanding students is an appreciation given by the boarding school to the students who have the highest scores. However, the election is usually still done subjectively and manually, and there is no support system in creating decisions, which make the selection process long and inaccurate. This study aims to implement a decision support system in determining outstanding students at Mamba'ussholihin Islamic Boarding School predetermined with criteria. The process of selecting uses the method Analytical Hierarchy Process (AHP) for weighting criteria and Operational Competitiveness Rating Analysis (OCRA) for ranking. The OCRA value obtained is in the form of Pi, which is ranked to get the best students. The findings show that the error consistency level is less than 10% and the consistency index value is accepted, so that it can be used as an initial weight with a relative number = 1.  After calculating the OCRA method from the initial 75 alternative data, the top 10 alternative data obtained are in the form of the value of Pi will be entitled to an award as an outstanding student, so by applying these two methods it can speed up the results of the decision, it does not take a long time and the results obtained are also precise.